PENGARUH KEMUDAHAN DAN KEAMANAN QRIS TERHADAP KEPUTUSAN PEMBELIAN UMKM KULINER: STUDI KASUS PENGUNJUNG CFD PALANGKA RAYA - Krisna, Krisna; Sintani, Lelo; Borneo Poetra, Gema; Sukmani, Meylinda (Penerbit Lafadz Jaya, 2026)
Digital transformation in payment systems through the Quick Response Code Indonesian Standard (QRIS) has become a key pillar of MSME modernization in Indonesia. However, the adoption of this technology in dynamic public spaces such as Car Free Day (CFD) still faces challenges related to user perceptions regarding operational aspects and data protection. This study aims to empirically analyze the influence of QRIS ease of use and security on consumer purchase decisions at culinary MSMEs in CFD Palangka Raya. A quantitative research approach with a causal associative method was employed. Data were collected through questionnaires from 100 respondents selected using purposive sampling technique at the CFD Palangka Raya research site, with a Likert scale questionnaire instrument. The data analysis techniques applied included classical assumption tests and multiple linear regression analysis using SPSS statistical software to examine the relationships between variables both partially and simultaneously. The results indicate that the ease of use and security variables have a positive and significant influence on consumer purchase decisions. Simultaneously, both variables contribute 62.4% to the variation in purchase decisions, as indicated by the coefficient of determination (R²) value of 0.624. These findings suggest that the efficiency of transaction procedures and system security guarantees are the main determinant factors in strengthening public trust and interest in digital transactions in open public spaces.